Delusional-like syndrome in chronic traumatic situation – case report - Perzyńska-Starkiewicz, Aneta; Wójcicka, Anna (Current Problems of Psychiatry, 2011)
The case describes 47-year-old woman who was admitted to the Department of Psychiatry, at Medical University of Lublin, with the preliminary diagnosis of paraphrenia. Woman in the period of involution, untreated psychiatrically, has been sent to a psychiatrist by a monk, who wanted the woman to be recognized as a person chosen by God. Detailed psychiatric interview was conducted with the patient. A series of psychological tests included assessment of her intellectual capabilities and the existence of any organic changes in the brain, as well as an assessment and interpretation of the patient’s personality traits. It was found that full scale IQ is at a higher level than average intelligence, and there are no signs of organic brain damage. Psychological test results indicate (as the cause of difficulty of conducting the test) – abnormal personality traits. Based on the interview, psychiatric and psychological study, it was found that the disturbance presented by the patient was due to a non-psychotic compensatory syndrome. Abnormal patient’s utterances were defined as delusional-like fantasies. The patient was recommended to attend family therapy, which aimed at improving relationships within the family, and also supportive psychotherapy.